2005
DOI: 10.1177/0363546505278304
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Methodological Quality of Research Published in the American Journal of Sports Medicine

Abstract: Overall, there was a shift toward more prospective and randomized research designs published in The American Journal of Sports Medicine during 2001-2003 compared to 1991-1993, demonstrating an improvement in the methodological quality of published research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Efforts to evaluate the quality of therapeutic studies published in medical and surgical specialty journals have been reported [3,5,11,17,24,32]. The primary purpose of our study was to quantitatively analyze the orthopaedic subspecialty literature before, around, and after the introduction of LOE to orthopaedics to determine if the overall number and proportion of high-quality publications (Levels I and II) had improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to evaluate the quality of therapeutic studies published in medical and surgical specialty journals have been reported [3,5,11,17,24,32]. The primary purpose of our study was to quantitatively analyze the orthopaedic subspecialty literature before, around, and after the introduction of LOE to orthopaedics to determine if the overall number and proportion of high-quality publications (Levels I and II) had improved.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Is a similar pattern seen in each specific subspecialty journal? (3) What is the interobserver reliability of grading LOE?…”
Section: Introductionmentioning
confidence: 99%
“…46,52,78,105 These are not unique problems to those using the STROBE checklist, as other groups have identified reporting of bias and funding as substandard and have used other criteria, such as the Standards for the Reporting of Diagnostic Accuracy (STARD) and custom checklists. 11,15,97 The STROBE Statement was originally designed to give "guidance to authors about how to improve reporting of observational studies and [facilitate] critical appraisal and interpretation of studies by reviewers, journal editors and readers. "…”
Section: Strobementioning
confidence: 99%
“…The purpose of this manuscript is to review the best available evidence to answer the following clinical questions for treating the patient with an initial anterior shoulder dislocation: (1) does the data support a particular method of reducing a dislocated shoulder? (2) what is the best way to premedicate patients before reducing the shoulder?…”
mentioning
confidence: 99%